2021
DOI: 10.1111/1346-8138.16101
|View full text |Cite
|
Sign up to set email alerts
|

Managing chromoblastomycosis with acitretin plus imiquimod: A case report on the improvement of cutaneous lesions and reduction of the treatment time

Abstract: is a mycosis that affects the skin and subcutaneous tissues. The etiologic agent is a black yeast that belongs to the Chaetothyriales order and Herpotrichiellaceae family. This fungus lives in the soil and plants of tropical and subtropical countries. In Brazil, the main etiologic agent is Fonsecaea pedrosoi, additionally infections with Exophiala jeanselmei and Exophiala spinifera have been documented. 1 The infection occurs after a contact of the lesioned skin with black yeast.Classical treatment of CBM is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Imiquimod, functioning as a Toll-like receptor agonist, has demonstrated efficacy in treating external anogenital warts, actinic keratoses, and superficial basal cell carcinomas. Studies have indicated its benefits in CBM treatment by modulating immunity and shortening the treatment course [ 9 19 ]. In addition, imiquimod inhibits collagen synthesis by promoting the production of the Th1 cytokine TNF-γ, and also inhibits the Th2 cellular immune response by inhibiting the production of the Th2 cytokines IL-4, IL-5, etc., ultimately controlling scar hyperplasia [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod, functioning as a Toll-like receptor agonist, has demonstrated efficacy in treating external anogenital warts, actinic keratoses, and superficial basal cell carcinomas. Studies have indicated its benefits in CBM treatment by modulating immunity and shortening the treatment course [ 9 19 ]. In addition, imiquimod inhibits collagen synthesis by promoting the production of the Th1 cytokine TNF-γ, and also inhibits the Th2 cellular immune response by inhibiting the production of the Th2 cytokines IL-4, IL-5, etc., ultimately controlling scar hyperplasia [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the neglected tropical diseases caused by saprophytic melanized fungi, CBM is one of the most prevalent; its etiological agents live in association with the plants that agricultural and logger workers manipulate during their work, and after an injury, they access the skin [4,27,28]. After infection, the fungi differentiate into muriform cells within phagocytes, becoming spherical and pigmented [8,29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with such combinations presented a rapid and sustainable reduction in the appearance of large verrucous plaques, which facilitated and reduced the treatment time with classic antifungals. By reducing the time of classical treatment, the risk of side effects caused by prolonged use of these medications was reduced, as well as promoting a rapid improvement in the quality of life and self-esteem of these patients [15,21,33].…”
Section: Discussionmentioning
confidence: 99%